2013
DOI: 10.1111/bjir.12010
|View full text |Cite
|
Sign up to set email alerts
|

E‐Communications: An Aspect of Union Renewal or Merely Doing Things Electronically?

Abstract: Drawing on questionnaire‐based survey data and web‐based data, this article examines the introduction of virtual branch websites within 12 branches of UNISON. The article situates e‐communications within a union communications strategy from the perspective of union members and shows how the virtual branch websites contribute to aspects of union renewal including organization and participation, union democracy and the conduct of industrial disputes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 16 publications
2
48
1
Order By: Relevance
“…Greene et al 2003;Pulignano 2009;Whittall et al 2009). A study of Unison's virtual branches in the United Kingdom confirmed the importance of remote engagement for atypical members, although sustaining such initiatives requires considerable support and resources (Kerr and Waddington 2013). A study of Unison's virtual branches in the United Kingdom confirmed the importance of remote engagement for atypical members, although sustaining such initiatives requires considerable support and resources (Kerr and Waddington 2013).…”
Section: Background: Ict In Union Communicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Greene et al 2003;Pulignano 2009;Whittall et al 2009). A study of Unison's virtual branches in the United Kingdom confirmed the importance of remote engagement for atypical members, although sustaining such initiatives requires considerable support and resources (Kerr and Waddington 2013). A study of Unison's virtual branches in the United Kingdom confirmed the importance of remote engagement for atypical members, although sustaining such initiatives requires considerable support and resources (Kerr and Waddington 2013).…”
Section: Background: Ict In Union Communicationsmentioning
confidence: 95%
“…As Kerr and Waddington (2013) note, online communication initiatives usually come along debates of renewal in union structures and democratic processes. Hence, the Internet cannot only be treated as an add-on that is likely to enhance communications but also as an element of union transformation.…”
Section: Background: Ict In Union Communicationsmentioning
confidence: 99%
“…(10) This strongly reminds of Kerr and Waddington [23]'s study of UNISON. Online participation in the Green Party might also start out with limited uptake in the beginning followed by a steady rise of participation by previously underrepresented groups.…”
Section: Use Of Technologymentioning
confidence: 66%
“…A study of the introduction of virtual branches in UNISON showed that a transition to online processes is surprisingly complicated [23]. Although nowadays an email address is typically collected along with address information, the union was founded before the internet, and thus did not have this data for all their members.…”
Section: The Internet In Organisationsmentioning
confidence: 99%
See 1 more Smart Citation